Are point-of-care urine albumin–creatinine ratio measurements accurate in the critically ill?. Issue 6 (November 2021) - Weinel, L.; Summers, M.; Poole, A.; Chapple, L.
Abstract: Background: In the critical care environment, elevated albuminuria values show capacity to reflect illness severity and predict mortality and hence assessing albumin/creatinine ratio (ACR) at the bedside has potential clinical benefit Point-of-care (POC) analysers offer rapid results but may be less accurate then laboratory analysis. Methods: Critically ill adult patients with a urinary catheter in situ had albumin, creatinine, and ACR measurements performed via laboratory and POC analysis. Data are presented as mean (standard deviation) or median [interquartile range]. Measurement agreement was assessed by Lin's concordance correlation coefficient, Bland Altman 95% limits of agreement, and classification by Cohen's kappa statistic. Results/Findings: Albumin, creatinine, and ACR analysis was performed for 30 patients. Lin's correlation coefficient showed 'substantial' agreement for albumin and ACR and 'almost perfect' agreement for creatinine for POC vs laboratory analysis. POC vs laboratory analysis also showed poor agreement for identification of normal ACR (>1 mg/mmol) and mild urine ACR (1–3 mg/mmol) and 'substantial' agreement for moderately increased urine ACR (3–30 mg/mmol). Conclusions: ACR POC values appear to provide an accurate and rapid method that has potential to provide an early indication of injury severity and mortality risk in the critically ill.